Analisis Pengaruh Orientasi Pasar, Inovasi Produk, Dan Digital Marketing Terhadap Kinerja Pemasaran (Studi Kasus pada UMKM diwilayah Kecamatan Gucialit Kabupaten Lumajang) - Assidiqi, Ahmad Hasbi; Malikah, Anik; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The purpose of this study is to analyze the influence of market orientation, product innovation, and digital marketing on the marketing performance of MSMEs in Gucialit District, Lumajang Regency. The research method used is quantitative with an explanatory research approach. Data were collected through questionnaires distributed to 60 culinary MSMEs in Gucialit District that have implemented product innovation and used social media in their marketing. Data analysis was conducted using multiple linear regression. The results show that market orientation has a significant positive effect on MSME marketing performance, with MSMEs with high marketing performance more likely to use market orientation strategies. Product innovation also has a significant positive effect. Furthermore, digital marketing contributes significantly to marketing performance, meaning that the higher the use of social media in marketing, the higher the marketing performance. These results provide implications for the importance of improving MSME marketing performance and the need for support from government agencies to improve product innovation and digital marketing. Keywords: Marketing Performance, MSMEs, Market Orientation, Product Innovation, Digital Marketing, Social Media, Multiple Linear Regression.